High expression of c-Myc in chronic lymphocytic leukaemia with t(8;14)(q24.1;q32): A case report. (September 2020) - Nagaharu, Keiki; Izumi, Takuya; Ueda, Mari; Usui, Eiji; Shikami, Masato; Ohishi, Kohshi; Tamaki, Shigehisa
Highlights: Overexpression of c-Myc is observed in high risk or transformed CLL. Because of rarity, the prognostic value of c-Myc / IgH in CLL has been undefined. CLL with t(8;14) showed higher c-Myc expression than CLL with normal karyotype. c-Myc / IgH translocation in CLL may be poor prognosis due to c-Myc overexpression.